Therapeutik Therapy Group for Stimulates Toddler of Mental Health - Betie Febriana; Dwi Heppy Rochmawati; Wahyu Endang Setyowati (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Health promotion for children in society still focuses on the physical, while psychosocial stimulation for children is still not optimal. This is because there are still many parents who are not aware of the importance of children's mental health, or they are people who realize it but it turns out to be too late. This condition results in children experiencing limitations in obtaining their rights at their age as a result, mental development can also be delayed or disrupted. Therefore, appropriate stimulation is needed provided by parents as caregivers to children. The aim of this community service is to improve the development of toddler children and the abilities of parents through therapeutic group therapy for toddler children in the Bandarharjo sub-district. This therapy consists of family psychology, namely education that stimulates the mental development of toddlers in parents and therapeutic group therapy, namely therapy that involves families with the same needs. This therapy consists of 6 phases, namely autonomy stimulation, motor, cognitive, emotional, psychosocial and finally the experience sharing phase.  The results achieved after being given child therapy show an increase in development and good changes in parents' ability to stimulate their toddlers in terms of cognitive and skills.